PENINGKATAN KEMAMPUAN SPEAKING MELALUI MODEL â€œTRIPLE Pâ€ - Ernati, Ernati (English Department FBS UNP, 2009)
This article aims at describing the improving of studentsâ€™ speaking skills trough PPP model (Triple P model). This model can encourage the students to speak English in the teaching learning process especially in speaking class. This is indicated by the improvement of studentsâ€™ creativity on teaching learning process in speaking class, their ability to express their own ideas, and their ability to interact or communicate with their friends. Â This model covers three activities; presentation, practice and production. So, it is wise for the English teachers/lectures to consider implementing this â€œTriple Pâ€ model in teaching speaking. Key words/ Phrases: speaking, triple P model, English, presentation, practice, production